На краю Ойкумены: роман / И. Ефремов - Ефремов Иван Антонович (Библиотека приключений, 2007)
Экземпляры: ф.16 (30.07.2008) / Инвентарный номер: 41527 / Цена: 80.41 / Авт.знак: Е 92 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4